Prospecção de bactérias lácticas para uso como probióticos e avaliação do efeito protetor em modelo murino de mucosite intestinal induzida por 5-FU - Nina Dias Coelho Rocha (2020)
The benefits exerted by probiotics have driven a series of studies in search for new strains with this potential. In this context, this study aimed to identify and characterize 21 new strains provided from different environments based on tests for evaluation of probiosis suggested by guidelines of regulatory agencies for further verification of the protective effect in murine model of mucositis induced by 5-fluourouracil (5-FU). Identification by MALDI-TOF revealed that all strains belong to the group of lactic bacteria (BLs), belonging to the genera Lactobacillus, Lactiplantibacillus, Lacticaseibacillus, Pediococcus and Enterococcus. In vitro safety tests were performed through the analysis of antibiotic resistance, mucin degradation and hemolytic potential and efficacy and functionality tests, through the resistance of the strains to bile salts, tolerance to acid pH, production of antimicrobial substances, adhesion and immune stimulation in Caco-2 cells. None of these criteria were excluding regarding the classification of the strains as probiotics, once all of them presented good parameters in prospection. Four of them belonging to different species were initially directed to in vivo studies, being Lacticaseibacillus paracasei Lpa1 (Lactobacillus paracasei Lpa1), Enterococcus faecalis Efc15, Lactiplantibacillus plantarum Lpl19 (Lactobacillus plantarum Lpl19) and Lactobacillus crispatus Lc21). When administered to the animals without the induction of mucositis, all strains showed similar parameters to the control animals, suggesting non-toxicity. However, the four were not able to significantly prevent weight loss, reduced water and food consumption, reduction of intestinal villi and inflammation, characteristic of the disease. However, even if they are not effective in the treatment of intestinal mucositis, the potential of these strains in other disease models and applications cannot be excluded. In this way, the present study opens up a range of lines of research to explore the role not only of the four strains tested in vivo, but also of all others that showed characteristics suggestive of probiosis in prospecting.